Duty rosters and workloads of obstetricians in Germany: results of a Germany-wide survey = Dienstmodelle und Arbeitsbelastung der geburtshilflich tätigen Ärzte in Deutschland : Ergebnisse einer deutschlandweiten Umfrage - Neimann, Johannes; Schott, Sarah (Geburtshilfe und Frauenheilkunde, 2017)
Compiling a daily hospital roster which complies with existing laws and tariff regulations and meets the requirements for ongoing professional training while also taking the legal regulations on the health of employees into account makes planning the duty roster a challenge. The aim of this study was to obtain a realistic picture of existing duty roster systems and of the current workloads of obstetricians in Germany.